Inventory of Distorted Thoughts about Women and the Use of Violence-Revised (IPDMUV-R): Psychometric properties - Echeburúa, Enrique; Amor, Pedro J.; Sarasua, Belén; Zubizarreta, Irene; Holgado-Tello, Francisco P. (Anales de Psicología / Annals of Psychology, 2016)
Men who batter are often affected by cognitive distortions related to gender roles and the legitimization of violence as a valid way to solve conflicts. The objectives of this research were: to analyze the psychometric properties of the Inventory of Distorted Thoughts about Women and the Use of Violence-Revised (IPDMUV-R), to delete nonupdated items and to compare the predictive ability of the revised version (IPDMUV-R) with other measures of the nomological network. The sample consisted of 463 men (241 batterer men and 222 men of the normative population), with a mean age of 41.22 years (SD=11.34). The results showed good fit indices for a unidimensional structure of IPDMUV-R (new version of 20 items) with an alpha of .747 (higher than the original 3 version of 29 items). The score of IPDMUV-R showed statistically significant correlations with self-reports which measure social desirability and ambivalent sexism. When analyzing the cutoff points to differentiate between batterer men and the normative group, the IPDMUV-R had a higher discriminative ability compared to IPDMUV and hostile and benevolent sexism dimensions. To conclude, an instrument with adequate psychometric properties to detect cognitive biases in violent men against the partner is presented. This instrument is useful for clinical purposes.